Потерянные иллюзии в автобиографической прозе князя И. М. Долгорукова (1764 – 1823) - Gigli, Rebecca (Lyuboslovie, 2024)
Prince I. M. Dolgorukov (1764–1823) was an interesting writer and figure of the Russian culture of the late 18th and early 19th centuries. His life path was like that of many young noblemen of the period. Full of hopes for a bright future, he had to face a non-idyllic reality. I. M. Dolgorukov turned his juvenile (and not only) illusions into a central theme of his autobiography, entitled “Povest’ o rozhdenii moyem, proiskhozhdenii i vsey zhizni”. This article aims to demonstrate that autobiographical prose became for the prince a means of overcoming the disappointments of his “lost illusions”, by revealing the deceptions behind illusory realities such as the world of service and the court. Moreover, the analysis of I. M. Dolgorukov’s ego-text illustrates the apologetic intentions of the writer in transforming his illusions into a leitmotiv. By thematizing the latter, Ivan Mikhaylovich justifies the lack of the expected successes in his life and career. In fact, the prince systematically shows how, both in the army and in the imperial bureaucratic system, his hopes of serving the emperor with devotion are always destroyed due to the corruption that surrounds him. The present study highlights that the theme of illusions is used in the author’s autobiographical narration with educational aims as well. From his own personal experiences and illusory ideals and expectations, I. M. Dolgorukov draws life lessons for his descendants. Finally, the article emphasizes that Self-writing itself can be considered a form of illusion with which the autobiographer tries to fight the passage of time and to make sense of his past.